Atypical aHUS: State of the art. Issue 1 (September 2015) - Nester, Carla M.; Barbour, Thomas; de Cordoba, Santiago Rodriquez; Dragon-Durey, Marie Agnes; Fremeaux-Bacchi, Veronique; Goodship, Tim H.J.; Kavanagh, David; Noris, Marina; Pickering, Matthew; Sanchez-Corral, Pilar; Skerka, Christine; Zipfel, Peter; et al.
Highlights: aHUS is an ultra-rare group of diseases defined by thrombocytopenia, anemia and renal failure. The majority of patients have genetic abnormalities that impair cell surface control of complement. Eculizumab, a monoclonal antibody to C5, has drastically reduced the mortality aHUS. Long-term therapy for aHUS requires further study. Abstract: Tremendous advances in our understanding of the thrombotic microangiopathies (TMAs) have revealed distinct disease mechanisms within this heterogeneous group of diseases. As a direct result of this knowledge, both children and adults with complement-mediated TMA now enjoy higher expectations for long-term health. In this update on atypical hemolytic uremic syndrome, we review the clinical characteristics; the genetic and acquired drivers of disease; the broad spectrum of environmental triggers; and current diagnosis and treatment options. Many questions remain to be addressed if additional improvements in patient care and outcome are to be achieved in the coming decade.